SEA practical application of science. (Romanian Foundation for Business Intelligence, 2013)
The journal is divided into six fascicles: 1. Economic experiences, 2. Applied and formal sciences, 3. Health and medical management, 4. Social and natural sciences, 5. Tourism, sports and leisure, and 6. Arts, education and humanities.